Intensi Job Hopping pada Generasi X, Y dan Z di Kota Surakarta - Erli Arlita; Putri Oktovita Sari (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The phenomenon of job hopping has become an increasingly relevant issue among Generations X, Y, and Z. In Surakarta, the phenomenon of job hopping is influenced by various factors. For Generation Y, the main factors influencing job hopping are work pressure, the desire to increase income, work location, and relationships with superiors. For Generation Z, job hopping is influenced by factors such as poor work-life balance, job dissatisfaction, and a lack of alignment with work values. For Generation X, job hopping is influenced by the desire for career development, salary and compensation, the search for a more positive work environment, a lack of opportunities for learning and development, the search for new challenges, and economic conditions. This study aims to analyze the differences in job hopping intentions among Generations X, Y, and Z in Surakarta City. This study uses quantitative data with primary data sources, namely the results of questionnaires distributed to respondents. The population of all Generation X, Y, and Z employees in Surakarta City is 271,426 people. The sample consisted of 399 respondents, with 133 respondents from each generation, using purposive sampling. Data collection was conducted by distributing questionnaires. Data analysis was performed using ANOVA. The results showed that there was a significant difference in the level of job hopping intention between Generation X, Y, and Z in Surakarta City. The highest job hopping intention among the three generations was found in Generation Y